Computer simulation of obtaining thin films of silicon carbide - Galashev, Alexander Y; Abramova, Ksenia A (Physical chemistry chemical physics : PCCP, 2023)
Silicon carbide films are potential candidates for the development of microsystems with harsh environmental conditions. In this work, the production of high-purity silicon carbide films by the electrolytic method is reproduced in a computer model. Single-layer SiC films were deposited on nickel, copper, and graphite substrates. The kinetic and structural characteristics related to the Si and C atoms in this compound are presented. The coefficient of self-diffusion of C atoms on all substrates is higher than that of Si atoms. In addition, the diffusion of atoms on a graphite substrate occurs much more intensively than on metallic (Ni and Cu) substrates. The first maximum of the radial distribution function ( ) is at a shorter distance when the film is deposited on the graphite substrate. A detailed analysis of the structure, based on the construction of Voronoi polyhedra, indicates that the degree of crystallinity of the film increases when changing the substrate in the order from nickel to graphite. The resulting SiC films are subject to local stresses, the strongest of which appear on the copper substrate, however the average stresses in the film do not appear to be high.